Multiscale recycling rare earth elements from real waste trichromatic phosphors containing glass. (20th November 2019) - Liu, Hu; Li, Shiyin; Wang, Bo; Wang, Kun; Wu, Ruize; Ekberg, Christian; Volinsky, Alex A.
Abstract: In this study, desilication, decomposition, and acidolysis were used to recycle rare earth elements (REEs) from real waste trichromatic phosphors containing glass at laboratory and pilot plant scales. The effects of pre-sintering temperature, sieving, alkaline leaching conditions and alkaline fusion temperature on removal of glass and recovery of REEs were investigated. About 88% of glass fragments in the original matrix were removed after dry sieving through a 0.05 mm mesh sieve and leaching by 5 mol/L NaOH solution at 90 °C for 4 h at the appropriate 5:1 liquid-solid ratio. The blue and green phosphors were decomposed by alkaline fusion at 600 °C for 2 h. Y, Eu, Ce and Tb-rich solutions were respectively obtained by the two-steps acidolysis. The total leaching rate of REEs reached 94%, while the rates of Y, Eu, Ce, and Tb were 96%, 99%, 81%, and 92%, respectively. Furthermore, in the ton level industrial pilot, the successful application of this approach increased the recovery of the REEs up to 90% compared with the existing technology. Except for the fixed capital investments and taxes, this approach showed positive economic feasibility, since the savings are 1115 €/ton. Therefore, recycling of REEs from waste phosphors is one of the cleaner and economical ways to balance the demand and supply of REEs outside of China. Graphical abstract: Image 100